Optimization of halal vinegar production from pineapple peel using response surface methodology (RSM) / Nadya Hajar - Hajar, Nadya (2015)
This study was focused on fermentation process of halal vinegar from pineapple peel.The objectives of this study were to study the physiochemical properties of pineapple peel extract variety N36, to optimize the alcohol yield during alcoholic-making process and acetic acid yield during vinegar-making process using Response Surface Methodology (RSM), to minimize the contents of alcohol and acetaldehyde compounds in vinegar. The physicochemical properties of the pineapple peel extract variety N36 for three different ripening stages indexes 1, 2 and 3 was determined before the fermentation processes. It was found that the physicochemical properties: TSS, pH values, TA, absorbance and pulp content were significantly increased at 50/0 level with the increased in ripening stages. The pineapple peel index 2 was selected as carbon source in this study. Bio-ethanol and acetic acid fermentation processes was carried out by controlling fermentation without addition of foreign substances. The optimum bio-ethanol production concentration of 8.637% (v/v) was determined, The optimum condition were 14% (v/v) inoculum concentration, pH 6, TSS 22°Brix, incubation temperature 26°C and 30 hours of incubation time. The significant regression equation or model at the 5% level with correlation value of 99.96% was also obtained. The optimum acetic acid concentration 4.238% was determined at the optimum condition of 13% inoculum concentration, pH 3.4, incubation temperature 30°C and incubation time 14 days. The significant regression equation or model at the 5% level with correlation value 99.96% was also obtained. Based on the HPLC analysis for ethanol detection, it has been proven that ethanol presence at the end of vinegar production can be reduced up to 0.59% (v/v).